Analisis dan Implementasi Software Defined Networking (SDN) untuk Automasi Perangkat Jaringan - Riski Amalia; Toibah Umi Kalsum; Riska Riska (Fakultas Teknik Universitas Hamzanwadi, 2021)
This study aims to build a network automation infrastructure by implementing a Software Defined Networking (SDN)-based web application to facilitate network administrators in implementing a web-based controller system for network devices by optimizing the configuration, management and operation time of network devices. This research uses action research method. In the action research method, researchers can describe, interpret and explain a condition at the same time as carrying out interventions aimed at improvement or participation. The results of this study indicate that the design and implementation of a Software Defined Networking (SDN)-based web application for network device automation using the python programming language with the paramiko library and the django framework can be applied to network infrastructure, so that with the application of SDN on network device automation applications can perform controllers. centralized network devices, so that configurations of many routers can be optimally carried out on a single Software Defined Networking (SDN) based web application.